THE USED OF EUPHEMISM IN ONLINE MEDIA: ANALYSIS OF THE NEWS HEADLINE REGARDING SENSITIVE ISSUE GAZA ISSUE IN THE JAKARTA POST - Lira Mey Nisa; Stevhany Christiani Siahaan; Satyawan Reinhard Tobing; Deniela Yoshelyn Simarmata; Grace Fanesya Ginting; Meisuri (Adisam Publisher, 2025)
This study examines the strategic use of euphemisms in news headlines regarding the Gaza conflict published by The Jakarta Post. Euphemism functions as a linguistic tool that mitigates the impact of sensitive or politically charged topics, shaping public perception and discourse. Using Allan and Burridge theory (1991) framework, the research categorizes euphemistic expressions found in 39 headlines and identifies prevalent strategies such as one-for-one substitution, technical jargon, understatement, and circumlocution.